2003
DOI: 10.1023/a:1024486716497
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Four single nucleotide polymorphisms (SNPs) and a variable number of tandem repeats (VNTR) polymorphism located within disease associated/causing genes were typed in four populations of different tribal and ethnic affiliation from the Sudan. The genotype and allele frequencies were compared with those of other groups from published and unpublished data of world populations. The combined Sudanese sample conformed with Hardy-Weinberg equilibrium (HWE) expectation. However, population sub-structuring according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Even if the positively selected substitutions are advantageous, it could be randomly lost over time due to the bottleneck effect. By contrast, the neutral substitutions could be easily fixed in small virus population over time by chance [58]. In our study, six codons with observed amino acid substitutions in DENV-1 E gene consensuses were under neutral genetic drift.…”
Section: Resultsmentioning
confidence: 64%
“…Even if the positively selected substitutions are advantageous, it could be randomly lost over time due to the bottleneck effect. By contrast, the neutral substitutions could be easily fixed in small virus population over time by chance [58]. In our study, six codons with observed amino acid substitutions in DENV-1 E gene consensuses were under neutral genetic drift.…”
Section: Resultsmentioning
confidence: 64%
“…p53 genotype distributions and allele frequencies of cervical cancer patients were compared with data from a healthy Sudanese control population published in 2003 (17) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Also, 36 formalin-fixed paraffin-embedded tissues (PETs) of non-cancerous samples were used as control for the presence of HPV. The control for the p53 study was previously published data of 253 Sudanese individuals from different ethnic groups (17). DNA was extracted from fresh tissues using TRIzol reagent protocol, while DNA from PETs was extracted using the JETQUICK kit (Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…We recently reported a striking risk association between the p53 arginine allele and breast cancer in Sudanese individuals [35], an unusual example of a common polymorphism with a major effect (OR= 13). This polymorphism has a known geographic pattern of a north South cline [36], which brings into consideration the geographical conditioning of the association between EBV and nasopharyngeal carcinoma endemicity, a known EBV associated tumour, around the tropics [37]. …”
Section: Discussionmentioning
confidence: 99%